School Achievement and Failure in Portuguese and Spanish Speaking Countries - Adelinda A. Candeias (Frontiers Research Topics, 2018)
This book is devoted to an increasingly important educational problem in the modern societies: school achievement and failure. School failure is presently a problem in developed as well as in developing countries. In the Spanish and Portuguese speaking countries in Europe and Latin America, school achievement and failure is consequently an important topic of political, social and scientific discussion. The following papers revise the latest research in the field, from the perspective of Psychology.